Using Binomial Trials Model for Examining the Judges’ Ratings of Cut Scores for a Criterion-Referenced Mathematics Test - Bani Ata, Zaid; Swalmeh, Yousef (Jordan Journal of Educational Sciences, 2008)
The study aimed at investigating the quality of judges’ rating of the cut score for a criterion-referenced test according to Angoff Method using Binomial Trials model. To achieve this purpose, marks of 110 tenth grade students on a 30- item criterion- referenced test in mathematics were analyzed. 15 judges’ ratings were also analyzed in three rounds of judgments. The results of the study indicated that there were significant differences (α = 0.05) among cut score estimates which can be attributed to judgment round. After eliminating the judges’ ratings which did not fit the model expectations, the differences among the estimated cut scores decreased in all rounds while there was an increase in the hit rate for students’ classification.